Crosstalk Between SMPDL3b and NADPH Oxidases Mediates Radiation-Induced Damage of Renal Podocytes - Azzam, Patrick; Francis, Marina; Youssef, Tarek; Mroueh, Manal; Daher, Alaa Abou; Eid, Assaad A.; Fornoni, Alessia; Marples, Brian; Zeidan, Youssef H. (Frontiers in Medicine, 2021)
Patients undergoing radiotherapy (RT) for various tumors localized in the abdomen or pelvis often suffer from radiation nephrotoxicity as collateral damage. Renal podocytes are vulnerable targets for ionizing radiation and contribute to radiation-induced nephropathies. Our prior work previously highlighted the importance of the lipid-modifying enzyme sphingomyelinase acid phosphodiesterase like 3b (SMPDL3b) in modulating the radiation response in glomerular cells. Hereby, we investigated the interplay between SMPDL3b and oxidative stress in mediating radiation injury in podocytes. We demonstrated that the overexpression of SMPDL3b in cultured podocytes (OE) reduced superoxide anion generation and NADPH oxidase activity compared to wild-type cells (WT) post-irradiation. Furthermore, OE podocytes showed downregulated levels of NOX1 and NOX4 after RT. On the other hand, treatment with the NOX inhibitor GKT improved WTs’ survival post-RT and restored SMPDL3b to basal levels. In vivo, the administration of GKT restored glomerular morphology and decreased proteinuria in 26-weeks irradiated mice. Taken together, these results suggest a novel role for NOX-derived reactive oxygen species (ROS) upstream of SMPDL3b in modulating the response of renal podocytes to radiation.